Celluar Folding Determinants and Conformational Plasticity of Native C-Reactive Protein - Lv, Jian-Min; Chen, Jun-Yao; Liu, Zu-Pei; Yao, Zhen-Yu; Wu, Yue-Xin; Tong, Cheng-Sen; Cheng, Bin (Frontiers in Immunology, 2020)
C-reactive protein (CRP) is an acute phase reactant secreted by hepatocytes as a pentamer. The structure formation of pentameric CRP has been demonstrated to proceed in a stepwise manner in live cells. Here we further dissect the sequence determinants that underlie the key steps in cellular folding and assembly of CRP. The initial folding of CRP subunits depends on a leading sequence with a conserved dipeptide that licenses the formation of the hydrophobic core. This drives the bonding of the intra-subunit disulfide requiring a favorable niche largely conferred by a single residue within the C-terminal helix. A conserved salt bridge then mediates the assembly of folded subunits into pentamer. The pentameric assembly harbors a pronounced plasticity in inter-subunit interactions, which may form the basis for a reversible activation of CRP in inflammation. These results provide insights into how sequence constraints are evolved to dictate structure and function of CRP.